The new physics and cosmology : dialogues with the Dalai Lama - Bstan-ʼdzin-rgya-mtsho, Dalai Lama XIV, 1935- (Mind and life series., 2004)
What happens when the Dalai Lama meets with five leading physicists and a historian? This book documents their discussions about theoretical quantum physics and Buddhist philosophy. This book is a contribution to the science-religion interface, and a useful explanation of our basic understanding of quantum reality.